Peran Pendidikan Agama Islam dalam Membentuk Etika Bermedia Sosial pada Generasi Z - M. Khoir Al Kusyairi; Husni Fuaddi (Jurnal Pendidikan Islam Indonesia, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) in shaping social media ethics among Generation Z and to identify Islamic values ​​relevant to guiding the behavior of the younger generation in the digital space. The study employs a qualitative approach using a literature review method. Data were obtained through an examination of scholarly journal articles, previous research findings, and literature relevant to Islamic Religious Education, character education, digital literacy, social media ethics, and Generation Z. The data were analyzed using a descriptive-analytical method by identifying, categorizing, comparing, and synthesizing relevant research findings. The analysis results indicate that PAI plays a strategic role in shaping social media ethics by reinforcing faith (aqidah), moral character (akhlaq), responsibility, honesty, verification (tabayyun), polite communication, respect for others, and self-control. PAI should not merely be treated as a vehicle for imparting religious knowledge; rather, it needs to be contextualized within the digital life experiences of Generation Z. Integrating digital literacy with Islamic values ​​enables learners to filter information, consider the consequences before uploading or sharing content, avoid behavior that demeans others, and utilize social media as a means for learning and disseminating positive values. Thus, PAI can serve as a moral and spiritual foundation for cultivating responsible digital citizens